2015
DOI: 10.3174/ajnr.a4277
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Contrast in the Evaluation of Meniere Disease: Understanding the Limits

Abstract: BACKGROUND AND PURPOSE:Studies describing endolymphatic hydrops in Menière disease after off-label intratympanic gadoliniumbased contrast have been limited by long acquisition times. We aimed to demonstrate the feasibility of post-intratympanic imaging on a 3T MR imaging system within a clinically tolerable acquisition time and to address potential pitfalls in acquisition or interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The presence of EH in other audiological disorders can be shown by IT administration: Hornibrook et al assessed the presence of EH not only in patients with definite MD (14/30 ears), but also in patients with other audiological disorders (3/45 ears), even if at a very low rate (6%) 29 . To address potential pitfalls in the acquisition or in the interpretation of the images, Bykowski et al used an 8 channel surface coils and acquired MR images 26 hours after monolateral IT administration in 6 definite MD patients 30 . Variable FLAIR inversion time images were used to determine the impact on fluid-suppression interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of EH in other audiological disorders can be shown by IT administration: Hornibrook et al assessed the presence of EH not only in patients with definite MD (14/30 ears), but also in patients with other audiological disorders (3/45 ears), even if at a very low rate (6%) 29 . To address potential pitfalls in the acquisition or in the interpretation of the images, Bykowski et al used an 8 channel surface coils and acquired MR images 26 hours after monolateral IT administration in 6 definite MD patients 30 . Variable FLAIR inversion time images were used to determine the impact on fluid-suppression interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…Although MRI is useful for EH diagnosis and exclusion of other diagnoses, the 2015 MD criteria emphasize clinical signs and symptoms in establishing a diagnosis. [76][77][78][79] EH has been documented using three-dimensional fluid-attenuated inversion recovery sequences in patients with MD, vestibular migraine, and isolated SNHL, and even in healthy subjects, so EH cannot be considered a specific finding in MD. 76 The use of intravenous gadolinium chelated-enhanced MRI allows visualization of EH.…”
Section: Vestibular Function Testsmentioning
confidence: 99%
“…Various MRI sequences and protocols have been used to study the inner ear following intratympanic injection(2). Nakashima et al devised a grading system using three-dimensional (3D) real inversion recovery imaging utilizing a ratio of the area of endolymphatic space to the vestibular fluid space (peri- plus endolymphatic spaces)(4,5).…”
Section: Discussionmentioning
confidence: 99%
“…We were able to achieve 0.5mm slice thickness resolution in 0.75s total scanning time. Bykowski et al utilizing 3-inch surface coil for 3T FLAIR MRI imaging showed 0.375×0.375mm in-plane FLAIR resolution at approximately five minutes imaging time, but highlighted a pitfall regarding overestimation of vestibular endolymphatic distention due to partial volume averaging(2). Finally, one study comparing IT to IV GBCA injection found IT to provide superior perilymphatic enhancement(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation